DEVELOPMENT OF INDIRECT ENZYME LINKED IMMUNOSORBENT ASSAY (ELISA) BASED SEROLOGICAL DIAGNOSTIC FOR HEPATITIS C VIRUS (HCV) DETECTION USING SYNTHETIC EPITOPE OF HCV NS3 PROTEIN - Steflandel Purba, William
Hepatitis C virus (HCV) is a virus that infects the liver and can cause liver cirrhosis and liver cancer. Indonesian health research data shows that there are three million people infected with HCV each year and 50% of them have the potential to develop into chronic diseases. However, preventive treatment for infection from the HCV virus has not been found, so handling infection is an important factor in the treatment of HCV infection. Therefore it is necessary to develop HCV detection which can recognize infection early. Indonesia itself still imports HCV diagnostic kits, both serology kits (ELISA) and molecules (based on nucleic acid amplification), so the ability to produce diagnostic kits independently is important to do. Previous studies have shown that NS3 is a protein in the HCV virus that can be an epitope candidate that can be used for the development of diagnostic tests. However, studies of the epitope's antigenicity have never been done. Therefore, in this study, the NS3 epitope antigenicity test was developed in a previous study. The testing method used in this experiment is the indirect Enzyme-Linked Immunosorbent Assay (ELISA). The first step is coating the epitope on a microtiter plate well for 16 hours at 4oC using a PBS buffer solution, then blocking the microtiter plate for 24 hours using PBST + skim milk solution at 4oC, then the ELISA test is carried out with a procedure which is the same as the kit Autobio commercial ELISA. As a negative control used negative HCV serum from healthy people. The samples tested came from materials stored in the serum of HCV and HIV coinfected patients at Hasan Sadikin General Hospital, West Java. In comparison, the Autobio commercial ELISA kit uses the same negative controls and samples as the developed test. In this study, the NS3 epitope antigenicity test was performed using the blood serum of patients treated with two dilutions and no dilution at all in the epitope concentration range of 0.1 ?g / mL - 25 ?g / mL. The results showed that double dilution and epitope concentration of 0.1 ?g / mL were still observed for the antigenicity of NS3 epitopes. However, further research is still needed to determine the detection limits, sensitivity, and specificity of the developed diagnostic kits.